PENINGKATAN KETERAMPILAN BERBICARA BAHASA INGGRIS MAHASISWA PROGRAM STUDI MANAJEMEN PEMASARAN POLITEKNIK NEGERI MANADO MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) - Wingston M.J Longdong; Selvie Ratna Ivone Mandang; Vincentius Pantow; Decire Dumingkan Wagiu (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2023)
Speaking skills are one aspect of the four language skills, including listening, speaking,reading and writing skills. To improve students' English-speaking skills, appropriatelearning methods/models are needed. In this study, the TPS (Think Pair Share)cooperative learning model was used. The aims of this study were: 1) To identify thefactors that influence the English-speaking skills of students of the MarketingManagement study program, Manado State Polytechnic. 2) Knowing the Englishspeakingskills of students of the Marketing Management study program, Manado State Polytechnicbefore and after using the TPS (Think Pair Share) cooperative learning model. The methodology used in this study is a qualitative descriptive method. Furthermore, for data collection methods using class action methods and data analysis using the Miles and Huberman method through the stages of preparation, application, data analysis and research report. Observations while it was found that students of the Manado State Polytechnic marketing management study program were generally not proficient in speaking English.